Changing Clinical Features of Subacute Sclerosing Panencephalitis (SSPE) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The early clinical features, age at onset, and relation to immunization of 32 patients (24 males, 8 females) with SSPE are reported from Grant Medical College, Mumbia, India.